1952
DOI: 10.1182/blood.v7.7.683.683
|View full text |Cite
|
Sign up to set email alerts
|

The Release of Leukocytes and Platelets from the Pulmonary Circulation by Epinephrine

Abstract: 1. The leukocyte and platelet contents of arterial and venous blood of 12 patients were determined simultaneously during and following the intravenous administration of 0.1 to 0.3 mg. of epinephrine, l-epinephrine or norepinephrine. 2. Within 30 to 60 seconds after the start of the epinephrine administration, an initial arterial leukocytosis and thrombocytosis occurred in 10 and 8 instances respectively and continued for at least 5 minutes before it declined. A leukocytosis also occurred in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

1953
1953
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(23 citation statements)
references
References 7 publications
4
18
0
1
Order By: Relevance
“…These results suggest that the CXCR4 gain-of-function mutation renders neutrophils less responsive to G-CSF-mediated egress signals. Consistent with this, quantification of the relative green fluorescent intensity in the BM also showed that the green fluorescent intensity remained relatively constant over the observation period, induce rapid demargination of neutrophils from the lungs (Bierman et al, 1952b). This set of experiments showed that indeed, epinephrine treatment increases neutrophil release from the lungs (Fig.…”
Section: Plerixafor Inhibits Trafficking Of Cxcr4 Mut Neutrophils To supporting
confidence: 76%
See 1 more Smart Citation
“…These results suggest that the CXCR4 gain-of-function mutation renders neutrophils less responsive to G-CSF-mediated egress signals. Consistent with this, quantification of the relative green fluorescent intensity in the BM also showed that the green fluorescent intensity remained relatively constant over the observation period, induce rapid demargination of neutrophils from the lungs (Bierman et al, 1952b). This set of experiments showed that indeed, epinephrine treatment increases neutrophil release from the lungs (Fig.…”
Section: Plerixafor Inhibits Trafficking Of Cxcr4 Mut Neutrophils To supporting
confidence: 76%
“…It has long been believed that the lung has the capacity to withdraw neutrophils from the blood into the pulmonary microvasculature and can deliver these cells back into the circulation when required (Bierman et al, 1952a). Indeed, neutrophils are rapidly released from the lung into the circulation within only seconds of epinephrine administration, indicating that the lung can serve as an important reservoir of these cells (Bierman et al, 1952b). Our own data revealed that CXCR4 inhibition triggers the release of neutrophils from the lung in both mice and nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the peripheral granulocyte count during and after the operation corresponds with our previous finding (36). Even if complement activation during the operation may cause the trapping of granulocytes in the lung capillaries (37), mobilisation of granulocytes from the reservoirs will cause the peripheral count to increase (38,39). Consequently, we did not register a drop in peripheral granulocytes, as seen during cardiopulmonary bypass ( 15), or haemodialysis (6) where the complement cascade is more rapidly activated,…”
Section: Discussionsupporting
confidence: 87%
“…109 Epinephrine also mobilizes platelets in asplenic dogs and rabbits. 33 As long ago as 1952, Bierman and his associates 10 demonstrated that following epinephrine injection, there was a rise in the arterial platelet count which preceded a rise in the peripheral venous count, suggesting release from the lung of sequestered platelets. Comparing first pass 51 Cr-labeled platelet and technetium-99m ( 99m Tc) labeled red cell indicator dilution curves in anesthetised dogs, Martin et al 67 demonstrated a slightly longer transit time for platelets.…”
Section: Platelet Distributionmentioning
confidence: 99%